Governance and Leadership - Fulop, Naomi J. (Elements of Improving Quality and Safety in Healthcare, 2023)
Lessons from service and system failures describe how governance and leadership each play a pivotal role in high-quality, safe care. This title is also available as Open Access on Cambridge Core.